Identification of Blood Protozoa in See-See Partridges (Ammoperdix Griseogularis) in Garmian Area/Kurdistan Region-Iraq - Mohammed Wahab; Shahnaz Ali; Nawzad Abdulrahman (مجلة الانبار للعلوم البيطرية, 2021)
Haemosporidians are intracellular protozoan parasites found inside the blood cells and tissues of avian hosts; they are almost worldwide distributed and occur in a variety of avian species, including see-see partridge birds. Blood samples were collected from 63 see-see partridges during a period extended from 19th November 2018 to 15th March of 2019 in the Garmian area/Iraqi Kurdistan region to detect and investigate the infection rates of haemosporidian parasites by microscopic examination using Giemsa stained smears. The results of the study showed that out of the total samples numbers 63 only 43 were found infected with haemoprotozoan parasites composing the overall infection rate of 68,25%, from 32 birds which were infected with Plasmodium spp. at a rate 50,79%, and 8 birds were infected with Haemoproteus spp. at a rate of 12,69%., the results also revealed that the rates of infection with these protozoan parasites vary substantially among the sampled locations. The present study showed that two haemosporidian genera (Haemoproteus spp. and Plasmodium spp.) were detected in see-see partridges in Kurdistan region-Iraq for the first time, and this type of bird is considered as a new host record for these haemoprotozoa in this area.